Trends and Developments in the Realm of Virtual Forest Visualization - Sunni Kanta Prasad Kushwaha; Hristina Hristova; Cyprien Fol; Tom Hands; Arnadi Murtiyoso; Arzu Coltekin; Anton Fedosov; Stefan Holm; Maximiliano Costa; Harald Bugmann; Verena C. Griess; Janine Schweier (Current Forestry Reports, 2026)
Purpose of the Review We aim to present virtual forest visualization in an accessible manner to help a broad audience understand this concept along with spatial data integration to create digital environments that closely replicate real-world forests. Such efforts are motivated by a multitude of reasons, from creating a virtual science laboratory to guiding real-world applications. The digital reconstruction of forests is an evolving field in forestry, with close connections to computer science and data science. The key considerations in visualization are also explained in detail which are crucial part of visualization like Input and output data along with challenges and constraints. Findings Recent advancements in digital sensing technologies have improved forest visualizations considerably. Data from techniques such as LiDAR and photogrammetry, along with other forest information, have facilitated the creation of highly detailed and accurate virtual forest models. These technologies not only capture the geometric structure of forests, but also enable the interactive exploration of different layers, from the canopy to the forest floor. The integration of these methods with Geographic Information Systems (GIS) and various user interfaces has further enhanced the spatial accuracy and contextual relevance of virtual forests. A major breakthrough in forest visualization is the incorporation of Extended Reality (XR) technologies, including Augmented (AR), Virtual (VR), and Mixed Reality (MR). These tools enable users to experience forest environments in a fully immersive way, without the need for physical presence. Given that some forests are prohibitively difficult to reach and navigate, and that some experiences can be greatly enriched by overlaying virtual elements onto the real world, XR experiences offer a valuable alternative to traditional data visualization approaches. Additionally, we also present four case studies to showcase the applications of visualization in the European forest context which can be applicable in the global context. Summary We examine key trends, developments, and challenges according to the global research in the use of 2D and 3D visualization for virtual forest experiences and present selected case studies. We describe the potential of virtual forest visualization for applications in forest management, conservation, education, and research. We also present an opportunity to utilize and develop further the scope of visualization using these latest technologies in forestry globally.